Visual communication and learning from COVID-19 to advance preparedness for pandemics - José de la Fuente; José Bedia; Christian Gortázar (Open Exploration Publishing Inc., 2020)
The currently ongoing coronavirus disease 19 (COVID-19) pandemic has affected globally human health and economy. Research in progress has shown facts associated with this disease and raised questions relevant for disease control and prevention. In this perspective, the collaboration between science and art in visual communication using the artwork "Enseñanza" ("Teaching") contributes to the representation of the lessons learned from COVID-19 and the way forward. To advance preparedness for current and future pandemics, the authors propose to address international collaborations, support to science, access to food supplies and health services, sustainable development and a "One Health" approach searching a balanced interaction of humanity with nature and a more holistic approach to disease prevention and control.